The Morehouse model : how one school of medicine revolutionized community engagement and health equity - Braithwaite, Ronald L., 1945-; Akintobi, Tabia Henry, 1976-; Blumenthal, Daniel S.; Langley, W. Mary, 1948- (Baltimore : Johns Hopkins University Press, 2020)
"Braithwaite and his coauthors, of Morehouse Medical School, describe the collaboration between community organizations and university faculty essential to public health and reliable research. They explain the Morehouse model of outreach in which citizen participation is a critical element for facilitating behavioral change in the community. Through case studies, exploratory research, surveys, and interventions, they provide lessons for advancing participatory research and promoting community health"--
Introduction to the Morehouse School of Medicine Model -- Social Accountability, Medical Education, and Public Health -- Community-Based Participatory Research (CBPR) -- Evolution of the Morehouse Model for Community Engagement -- Engaging Micropolitan and Rural Communities in Health Promotion and Disease Prevention -- Educational and Leadership Development -- For Communities, by Communities : The Strategic Engagement of Community Health Workers -- The Medical School of Tomorrow.
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: Morehouse School of Medicine; Morehouse School of Medicine; Morehouse School of Medicine; Public health -- Research -- Methodology; Public health -- Research -- Citizen participation; Community-based research; Medical colleges; Public Health -- methods; Community-Based Participatory Research -- methods; Schools, Medical; Community-Institutional Relations; Community Participation; Georgia; Santé publique -- Recherche -- Méthodologie.; Santé publique -- Recherche -- Participation des citoyens; Écoles de médecine.; Medical colleges; Community-based research; Public health -- Research -- Citizen participation; Public health -- Research -- Methodology